Leydig cell tumor of the testis with azoospermia and elevated delta4 androstenedione: case report. Issue 1 (December 2016) - Prasivoravong, J.; Barbotin, A-L.; Derveaux, A.; Leroy, C.; Leroy, X.; Puech, P.; Mitchell, V.; Marcelli, F.; Rigot, J-M.
Abstract Background Secreting interstitial cell (Leydig cell) tumors are rare. In adults, the clinical picture and steroid levels are variable. Case presentation This paper presents a case of left testicular tumor, showing azoospermia with normal serum level of total testosterone, collapsed FSH and LH, and high delta4 androstenedione. Histopathological investigation revealed a Leydig cell tumor. TESE allowed spermatozoa extraction and freezing. Testicular histology found hypospermatogenesis and germ-cell aplasia with interstitial fibrosis. Surgical resection of the tumor resulted in normalization of gonadotropins and fall in serum delta4 androstenedione to subnormal levels in the postoperative period confirming that the tumor was secreting delta4 androstenedione. It was hypothesized that high delta4 androstenedione resulted in intra tumoral 17 β-HSD overtaken by delta4 androstenedione or that 17 β-HSD activity in the tumor was different from that of normal Leydig cells. Three months after surgery sperm analysis found a complete recovery of spermatogenesis. A spontaneous pregnancy occurred 3 months after surgery and a girl was born. Conclusions In this case, the diagnosis of testicular Leydig cell tumor secreting delta4 androstenedione was made in a context of azoospermia. Résumé Introduction Les tumeurs testiculaires interstitielles (ou tumeurs testiculaires à cellules de Leydig) à expression endocrine sont rares. Chez l'adulte le tableau clinique et le bilan hormonal sont variables. Présentation du cas Cet article présente le cas d'une tumeur testiculaire gauche dans un contexte d'azoospermie. Le bilan hormonal montre des gonadotrophines effondrées, une testostéronémie normale et une delta4 androstenedione augmentée. L'examen anatomopathologique a mis en évidence une tumeur à cellule de Leydig. La TESE a permis l'extraction et la congélation de spermatozoïdes. L'histologie a retrouvé un aspect mixte d'hypospermatogenèse diminuée incomplète et d'aplasie. Dans les suites de l'orchidectomie partielle gauche les taux de gonadotrophines se sont normalisés ainsi que le taux de delta4 androstenedione. L'hypothèse physiopathologique est que l'augmentation de la delta4 androstenedione résulte de la sursaturation de la 17 β-HSD intra-tumoral ou que l'activité de la 17 β-HSD intra-tumoral est différente de celle dans les cellules de Leydig normales. Trois mois après la chirurgie, le spermogramme a montré une normalisation des paramètres spermatiques et une grossesse spontanée est survenue permettant la naissance d'une petite fille. Conclusion Dans ce cas clinique, le diagnostic de tumeur testiculaire à cellule de Leydig sécrétant de la delta4 androstenedione a été fait dans un contexte d'azoospermie.